BELAJAR SAMBIL BERMAIN: MENINGKATKAN LITERASI KEUANGAN SISWA SD MELALUI DRAMA SOSIO JUAL BELI - Arshy Prodyanatasari; Refki Marsida; Anita Maharani; Dahniar Widya Kharisma; Lea Tarissha Primanda (Merwinspy Publisher, 2025)
The introduction of currency to elementary school students is an important step in equipping them with the financial literacy skills needed for everyday life. This activity aims to provide a deeper understanding of the value of money, buying and selling transactions, and the arithmetic skills required for financial management. The community service activity (PkM) was carried out in March 2024 at SDN Bujel 3, Kediri City, with 43 student participants. The method used was Participatory Action Research with a socio-drama buying and selling strategy, which allowed students to directly interact with the concept of money in a fun and realistic situation. Through this game, students could learn to count and negotiate. The evaluation of the activity was conducted through the analysis of pre-test and post-test scores using Non-parametric Statistical Test, the Wilcoxon Test, due to the data not being normally distributed. The results showed a significant improvement in students' financial literacy skills, particularly in understanding the value of money, arithmetic skills, and managing buying and selling transactions. Students also showed improvement in social skills, such as interacting with peers in a buying and selling context. This activity proves that the participatory method, which combines socio-drama buying and selling, can be an effective tool in improving financial literacy in elementary school students. Additionally, this activity contributes positively to the development of life skills that are useful in everyday life.